A demand equation for West Malaysian imports - Mohammad Haji Alias (Universiti Kebangsaan Malaysia, 1978)
This paper reports an econometric study of a import function for West Malaysia using time-series data for the period 1960-1974. The theoretical basis of the investigation is a postulated behavioural relationship between the quantity of imports of goods and services and several explanatory variables namely relative prices, lagged imports and gross national product.